The one device : the secret history of the iPhone - Merchant, Brian (New York : Little, Brown and Company, 2017)
Describes how the inception of the iPhone has transformed society and skyrocketed Apple to the most valuable company in the world, detailing how the most current technological advances have become inseparable from everyday life.
"Odds are that as you read this, an iPhone is within your reach. But before Steve Jobs introduced us to 'the one device, ' as he called it, a cell phone was merely what you used to make calls on the go. Now, a decade after the iPhone hit shelves, our phones are our lifelines: our primary source of information, communication, and entertainment, our main connection to work, and a constant link to the people we love. How did the iPhone transform our world and turn Apple into the most valuable company ever? Journalist Brian Merchant reveals the inside story you won't hear straight from Cupertino--based on exclusive interviews with the hands that guided every stage of the iPhone's creation. This fascinating hidden history, by turns dazzling and dark, takes you from inside Apple's main campus at One Infinite Loop to nineteenth-century France to WWII America to twenty-first-century China, from the driest place on earth to a Kenyan pit of toxic e-waste, from the world's largest particle collider to deep inside Shenzhen's notorious 'suicide factories.' It's a firsthand look at how the bleeding-edge tech that makes the world work--from touchscreens to motion trackers to artificial intelligence--has made its way into our pockets and become inseparable from our Iives. The One Device is a road map for design and engineering genius, an anthropology of the modern age, and an unprecedented view into one of the most secretive organizations in history. This is the untold account, ten years in the making, of the device that changed everything."--Jacket.
Exploring new rich interactions. A smarter phone ; Minephones ; Scratchproof ; Multitouched -- Prototyping. Lion batteries ; Image stabilization ; Sensing motion ; Strong-ARMed ; Noise to signal -- Enter the iPhone. Hey, Siri ; A secure enclave ; Designed in California, made in China ; Sellphone ; Black market -- The one device.
Includes bibliographical references and index.
Keywords: Apple Computer, Inc. -- History; Apple Computer, Inc; iPhone (Smartphone) -- History; Smartphones; Smartphones; BUSINESS & ECONOMICS -- Industries -- Computer Industry; SCIENCE -- History; TECHNOLOGY & ENGINEERING -- Electronics -- Digital; iPhone (Smartphone); Smartphones; History